Interdialytic blood pressure variability and the risk of stroke in maintenance hemodialysis patients. Issue 29 (17th July 2020) - Cheng, Yue; Li, Yunming; Zhang, Fan; Zhu, Jun; Wang, Tao; Wei, Meng; Mo, Liwen; Li, Yi
Abstract : Abstract: Studies on nondialysis populations have linked visit-to-visit blood pressure (BP) variability (BPV) to cerebrovascular events and mortality. In view of the high prevalence of hypertension in hemodialysis patients, the predictive values of numerous factors for stroke, especially visit-to-visit BPV, were evaluated in this prospective cohort study. A total of 151 patients were enrolled in this study. The demographic features and various laboratory parameters were analyzed. At each routine hemodialysis visit, the predialysis, intradialysis, and post-dialysis BP measurements were systematically performed. We defined BPV using 4 metrics: standard deviation of the BP, coefficient of variation, average real variability (ARV), and variability independent of mean (VIM). Differences in the predialysis BPs from one treatment to the next (ie, interdialytic variability) and differences in the BPs from predialysis to post-dialysis (ie, intradialytic variability) were both studied in this work. Twenty-one patients developed stroke and 25 patients died. The multivariate Cox proportional hazards regression model revealed a significant relationship between stroke and the interdialytic BPV (both predialysis systolic BP variability and predialysis diastolic BP variability) and low-density lipoprotein-cholesterol (LDL-C). Our results indicate that a high interdialytic BPV is associated with an increased risk for stroke that is independent of several factors, including age, sex, antihypertensive medication use, and mean BP over time. There is potential that the optimal treatment goal for hemodialysis patients may be to reduce the interdialytic BPV rather than either the mean BP or the intradialytic BPV. Abstract : Supplemental Digital Content is available in the text